Dari mata turun ke hati: Mengembangkan sikap menghargai perbedaan dalam bingkai moderasi beragama - Gultom, Rogate Artaida Tiarasi (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
This article aims to offer a constructive idea about developing an attitude that respects differences, both in terms of theological perspectives and traditions, dogmatic views, church denomination membership, and even religion. The strengthening of religious fundamentalism triggers the occurrence of a religious pattern that is too fanatical and considers its views and groups to be the most correct, so they tend to judge differences using the judgment model. The idea offered is to internalize Jesus' teaching not to judge others excessively through the narrative of Matthew 7:1-5. This research is qualitative-descriptive, with a constructive approach related to the theme of “respect” and “non-judgmental” toward others. In conclusion, the church needs to continue to build fellowships or networks between Christians in different denominations, and between religious communities, and to develop a